Election registration system on system Z/mainframe - Nor Fazleen, Mohammad Nasir (2012)
Election Registration System helps system operators and system administrators to monitor and manage the registration for election activities easily without having problems in the server ability and the database.This system helps the system operator and system administrators to work in an efficient way without having so much trouble with the server down due to the overloaded users at a time by using the system i/mainframe.The system zlrnainfrarne refers to the zero downtime servers which can ensure that there will be no problem with the server even there are a lot of requests at a time.This ERS helps the system operators and system administrators to works faster in terms of updating,viewing and printing the data in the database.